Cytomegalovirus Esophagitis: Two Patients with Different Features - Huwi-Chun, Chao; Wen-Liang, Yu (Journal of Digestive Disorders And Diagnosis, 2016)
Two cases of CMV esophagitis presenting with distinct clinical and endoscopic features are presented. Diagnostic clues, histopathology, and antiviral therapy considerations are highlighted, emphasizing vigilance in immunocompromised hosts.
Keywords: Cytomegalovirus; Esophageal ulcer; Gastrointestinal bleeding